Superdiversity, population health and health care: opportunities and challenges in a changing world. (July 2019) - Phillimore, J.A.; Bradby, H.; Brand, T.
Abstract: Objectives: Ethno-national approaches to research public health and migrant outcomes have dominated for decades but lack efficacy in a globalised world and in view of the intractable nature of health outcome inequalities for migrant and minority groups. This article highlights some of the challenges and opportunities associated with a superdiversity perspective in public health research. Superdiversity and ethno-national approaches: Migration patterns have changed with more people arriving from more places and the diversification of diversity meaning that the ethno-national categories utilised in public health research have reduced explanatory potential. The example of maternal and perinatal mortality in the United Kingdom: Adjusting UK perinatal mortality rates by five ethnic groups based on assumptions of relationships between high levels of risk and ethnic groups masks the scale of inequality faced by groups wherein mortality rates are increasing and highlights some of the difficulties associated with using ethno-national classifications. A superdiversity perspective: A superdiversity approach moves beyond ethno-nationalism to socially locate groups focussing on commonalities and differences across spaces and characteristics and employing intracategorical or anticategorical approaches. Conclusions: Superdiversity brings new levels of demographic complexity and fluidity. Greater reflexivity is needed in diversity research with justification of classifications used for analysis necessary when research questions are developed. Highlights: Globalisation and associated superdiversification have resulted in challenges for public health provision and research. Superdiversity urges a move away from ethno-nationalistic approaches to sampling and explanation. Superdiversity encourages the consideration of which differences make a difference to individual and group health outcomes. Overreliance on ethno-national approaches can lead to structural and other differences being overlooked as explanatory factors. There are no established methods for researching superdiverse populations. Researchers should consider wide-ranging explanations for differential outcomes in advance of instrument design.